2018
DOI: 10.5455/annalsmedres.2018.11.253
|View full text |Cite
|
Sign up to set email alerts
|

The independent risk factors that affect the hospitalization of acute bronchiolitis

Abstract: Aim: The aim of this study is to find out the independent risk factors that affect the period of hospitalization in acute bronchiolitis. Material and Methods: The patients who were hospitalized with the diagnosis of bronchiolitis at the Pediatric Emergency and Intensive Care Unit were included. Results: 61 (64 %) of the patients were males and 34 (36%) were females. The median age of the patients was 7 (1.5-23) months. The median hospitalization period was 6 (3-18) days. Factors affecting prolonged acute bronc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Epidemiological evidence has shown that breastfeeding human milk is a protective factor against the development of multiple diseases, including AB, due to the high transmission of immunological factors present in breast milk. [23][24][25][26] A recent systematic review showed that exclusive and partial breastfeeding reduces the severity of the disease, length of hospital stay and supplemental oxygen requirement. This review demonstrated that hospitalized infants were signi cantly more likely to be breastfed for less than 6 months.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological evidence has shown that breastfeeding human milk is a protective factor against the development of multiple diseases, including AB, due to the high transmission of immunological factors present in breast milk. [23][24][25][26] A recent systematic review showed that exclusive and partial breastfeeding reduces the severity of the disease, length of hospital stay and supplemental oxygen requirement. This review demonstrated that hospitalized infants were signi cantly more likely to be breastfed for less than 6 months.…”
Section: Discussionmentioning
confidence: 99%